2021
DOI: 10.3390/met11101593
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Post Heat Treatments on Microstructures and Mechanical Properties of Selective Laser Melted Ti6Al4V Alloy

Abstract: The unique thermal history of selective laser melting (SLM) can lead to high residual stress and a non-equilibrium state in as-fabricated titanium alloy components and hinders their extensive use. Post heat treatment, as a classical and effective way, could transform non-equilibrium α’ martensite and achieves desirable mechanical performance in SLMed Ti alloys. In this study, we aimed to establish the correlation between the microstructure and mechanical performances of SLMed Ti6Al4V (Ti-64) by using different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
4
0
1
Order By: Relevance
“…Induction Hardening: This process involved heating the components using an induction coil, followed by rapid quenching in a water bath. The heating temperature and time were varied to study their effects on the mechanical properties of the components [19]. Laser Hardening: In this process, a high-energy laser beam was used to heat the surface of the components rapidly, followed by self-cooling in ambient air.…”
Section: Heat Treatment Techniquesmentioning
confidence: 99%
“…Induction Hardening: This process involved heating the components using an induction coil, followed by rapid quenching in a water bath. The heating temperature and time were varied to study their effects on the mechanical properties of the components [19]. Laser Hardening: In this process, a high-energy laser beam was used to heat the surface of the components rapidly, followed by self-cooling in ambient air.…”
Section: Heat Treatment Techniquesmentioning
confidence: 99%
“…Using high resolution digital image correlation, Book et al confirmed that strain accumulation occurs in lamellas with a major axis approximately 45 ° to the loading direction [38]. A key role of grain boundary α layers, where early damage preferentially occurs, was also suggested from several studies [12,32,39,40]. These different scenarios highlight the critical importance of the elongated morphology of prior β grains.…”
Section: Introductionmentioning
confidence: 96%
“…The laser metal deposition (LMD) technique is one of the most frequently used AM techniques in this context. As compared to more conventional applications, available pathways to achieve superior properties can be substantially reduced in repaired parts: preheated substrates, which allows to reduce residual stress [8], or post-processing heat treatments, which can be used to tailor microstructural features [9][10][11][12], can be prohibited for components such as titanium leading edges of organic matrix composite fan blades used in most advanced aero-engines. A comprehensive understanding of the relationships between processing parameters, microstructure and mechanical properties in as-built materials is then of critical importance.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Furthermore, due to the complex cyclic thermal history and the extremely rapid cooling, the heterogeneous microstructures including the prior β-grains, and acicular α' martensite formed in LPBF Ti-64 alloys. [37][38][39] The process parameters also played an important role in the microstructure of the LPBF Ti-64 alloys, which could directly determine the thickness of the α (α') laths. 40,41 Specifically, with the increase in the scanning speed, the acicular α (α') structure in LPBF Ti64 alloy could be gradually refined, and the microstructure transformed from equiaxed grains to columnar morphology grains.…”
Section: Introductionmentioning
confidence: 99%